Assessing Student’s Knowledge of the Health Risks of Plasticizer Exposure - Kyei , Akosua Fosua; Darkwa, Sarah (Asian Journal of Empirical Research, 2015)
This study assessed students’ level of awareness and knowledge in probable modes of exposure to plasticizers. A descriptive survey of 200 people (60 each of science and non-science students) in Senior High Schools, 60 Junior High School students and 20 food vendors in the Awutu Senya East Municipality, Central Region was conducted from November 2014 to March 2015. One hundred and twenty Senior High School students (30 males &30 females each from science & non science programmes), 60 Junior High School students (30 males & 30 females) and 20 (females) food vendors were purposively selected. Observation, interview and questionnaires were used to collect data which was analyzed using cross tabulations. A response rate of 88.5% was obtained. Findings showed 94% of the respondents had no knowledge of plasticizers and probable routes of exposure. The remaining students who had some knowledge of plasticizers and their routes of exposure obtained that knowledge from watching television. In conclusion, awareness and knowledge of plasticizers, possible routes of exposure to plasticizers and their associated health risks were found to be low among the students. Packaging materials used for packaging foods for the students were found to be the major routes of exposure to plasticizers.